Linfedema primário e outros defeitos congênitos diagnosticados em bovinos de 1964 a 2010 pelo laboratório de patologia veterinária da Universidade Federal de Santa Maria - Macêdo, Juliana Targino Silva Almeida e (2010)
In one research, cases of congenital lymphedema were observed affecting 17 Red Angus calves and their crosses from two farms in the central region of the state of Rio Grande do Sul, Brazil. Affected calves presented variable degrees of subcutaneous edema at birth, involving mainly the hind limbs, but also other body regions. The injection of methylene blue dye in a 5% solution into the interdigital space of the hind limbs of three affected calves and one normal control indicated an interruption of the lymph flow in the affected calves; this suggests a failure of the distal peripheral lymphatics to connect with the central trunks. At necropsy of three affected calves, subcutaneous edema was variably observed in the hind limbs, prepuce and ventral abdomen. Edema of body cavities was not observed. In two cases there was hipoplasia of the popliteal lymph nodes associated to dilatation of lymphatic vessels. DNA tests demonstrated that all affected calves were born from cows sired by the same bull suggesting an inherited basis for the disease. Furthermore unrelated cows of different breeds sired by Bull 1 delivered affected calves which suggest that condition is an autosomic dominant trait. Considering the large numbers of cows sired by Bull 1 relative few calves were affected; this could be explained by a low penetrance of the trait. In another research, cases of congenital defects (CDs) in cattle diagnosed at the Laboratory of Veterinary Pathology of the Federal University of Santa Maria from 1964 to 2010 were reviewed. During the studied period, tissues collected from the necropsy of 7,132 cattle were examined and 31 calves (0.4%) with CDs were found. These CDs were classified into 34 different types and ascribed to the body system primarily affected. The results of this survey indicate that the majority o CDs in cattle in the central Rio Grande do Sul are sporadic; nevertheless their continued study is important for determining the etiology and control.